Pandan Baru Sdn Bhd (Berinda Properties) / Wan Safirah Azyan Wan Mohamed - Wan Mohamed, Wan Safirah Azyan (Faculty of Business and Management, 2023)
From the quote we can say that if we don't dare to try something, we won't have anything to be proud of. Industrial training is one of the bigger opportunities for the students as it works to emphasize and develop working skills for them. As a student, there is no doubt that this field of work brings a new adventure in a very different environment to students. From this memorable and cherish able 6 months of training programmed at Pandan Baru Sdn Bhd, I would say that is the best decision I have ever made. Worth to share that this company is one of the stable and successful company in Malaysia and the purpose I am writing this industrial training report is to aim about my working experience throughout internship period, company's profile, the SWOT analysis of this company, some discussion that can be presented and my own recommendation that might be useful for more effective company development. During the period, I was given the opportunities to be placed in two departments which is in HR & Admin Department for 12 weeks and in Sales & Marketing Department also for 12 weeks. Both of departments bring unique experience and expertise that will be valuable in the future.